LncRNA PVT1 Mediates Antiapoptosis and 5-Fluorouracil Resistance via Increasing Bcl2 Expression in Gastric Cancer. (8th May 2019) - Du, Peizhun; Hu, Cheng'en; Qin, Yunyun; Zhao, Jing; Patel, Rajan; Fu, Yan; Zhu, Mengqi; Zhang, Wenhong; Huang, Guangjian
Abstract : Purpose . Plasmacytoma variant translocation 1 (PVT1) is a long noncoding RNA encoded by the human PVT1 gene, which has been verified to mediate tumorigenesis in gastric cancer. However, the underlying molecular mechanisms of PVT1 in gastric cancer (GC) remain largely unknown. Methods . The tumorigenic ability of PVT1 was verified by subcutaneous and orthotopic mouse models. Flow cytometry assay and TdT-mediated dUTP Nick-End Labeling staining were conducted to explore the effects of PVT1 on gastric cancer cell apoptosis. We investigated the relative gene and protein that are involved in apoptosis in real-time PCR and western blot assay. The resistance to 5- Fluorouracil (5-Fu) caused by PVT1 was evaluated using cell viability assay. Then, to confirm the effects of PVT1 on 5-Fu resistance, we conducted the Kaplan-Meier analysis based on three public databases. Results . We confirmed that PVT1 can promote the progression of gastric cancer. PVT1 inhibited the apoptosis of GC cells, which may account for its promotion on GC. We confirmed that PVT1 can regulate the expression of Bcl2 and enhance drug-resistance of gastric cancer to 5-Fu. Kaplan-Meier analysis showed that patients with high PVT1 expression do not experience survival related benefits from 5-Fu based chemotherapy; instead, therapy containing no 5-Fu chemotherapy can improve the first progression survival and overall survival of high PVT1 expression GC patients significantly. Conclusion . Our results showed that PVT1 can inhibit the apoptosis and enhance the 5-Fu resistance of gastric cancer through the activation of Bcl2. PVT1 has the potential to serve as an indicator to predict 5-Fu treatment resistance.